Functional movement screen test as an predictor for jumping tests performance and on-ice skating sprint in elite level ice hockey players - Baron, J.; Holub, M.; Stanula, A. (Journal of Kinesiology and Exercise Sciences, 2024)
Background. The main purpose of this research was to establish selected motor skills measured in off-ice and on-ice conditions in ice hockey players using the functional movement screen test, vertical jumps, and on-ice sprints. Material and Methods. The present study measured fifty-four (n=54) elite-level ice hockey players, competing in the top-level league in Poland (Polish Ice Hockey League, PHL) during the 2019/2020 season. Tests were divided into off-ice and on-ice protocols. The off-ice tests consisted of body composition measurements (including body weight, muscle mass, % of body fat), functional movement screening (FMS), measurements of jump height and power of the lower limbs, including countermovement jump (CMJ), squat jump (SJ), and drop jump (DJ). On-ice tests were divided into skating sprint testing measured in splits (0-10m, 10-30m), and total sprint between 0-30m. Furthermore, the maximal skating sprint was also measured between blue lines (15m). Results were correlated between FMS tests, vertical jump tests, and on-ice skating tests. The relationships between the variables were quantified using Pearson`s product-moment correlation. The aim of this study was to highlight off-ice protocols, which can best predict on-ice parameters. Fitness profiling involved division into forwards and defenders and the calculations were also performed for a whole group of hockey players. Results. The study showed a strong correlation between total points scored in FMS with the vertical jumps and skating sprints, especially in the defender group in CMJ jump height r = 0.69 (p < 0.001) and 30m skating sprint r = 0.7 (p < 0.001). Conclusions. The study found positive correlations between FMS tests and off-ice and on-ice parameters, showing that the FMS test could be used to predict ice skating performance.